“Those with many cattle were better off”: herd size preferences and perceived tradeoffs in the face of extreme events - J. Terrence McCabe; Amy Quandt; Paul W. Leslie (Pastoralism, 2025)
African rangelands are changing rapidly due to land use change, the erosion of traditional social institutions, and increasing concern about extreme events. These changes pose a challenge to the resilience of pastoral people, their herds, and the rangelands that they inhabit. Despite these changes, debates in academics and policy continue about the optimal herd size to maintain pastoral livelihoods while avoiding environmental degradation. In this study, we draw from 33 focus group discussions with Maasai men and women in northern Tanzania to explore herd size preferences for coping with extreme events. Study participants expressed a preference for larger herds, with the primary rationale being enhanced ability to cope with drought and other extreme events. Those with large herds are better able to sell a few animals, and this money can directly benefit the family and help feed the rest of the herd through purchasing supplemental feed in the form of pumba, crop residues, or access to farmland for grazing crop residues. These findings highlight new pathways and reasons that large herds can be useful. Chief among these is having enough animals to sell to buy supplemental feed and yet sustain a viable herd. Recognizing the cultural importance of livestock to Maasai along with local perspectives on livestock herd numbers will help in supporting culturally relevant adaptation policy and practice. For example, policies and projects could focus on enhancing resilience through facilitating the saving and storing of crop residues or helping maintain livestock prices during extreme events.